Classical Conceptions of Moral Education: A Comparative Analysis of Al-Ghazali’s Tazkiyatun Nafs and Ibnu Miskawaih’s Tahdzib al-Akhlaq and Their Relevance to the Contemporary Youth Moral Crisis - Armalena Armalena; Ali Amran; Erman Erman; Tamrin Kamal; Firdaus Firdaus (LPPM Universitas Muhammadiyah Sumatera Barat, 2026)
Adolescence in the current digital era is confronting a complex moral crisis and value disorientation, manifested in phenomena such as cyber-bullying, hedonism, and identity insecurity. This research aims to reconstruct a holistic moral education model by synthesizing the classical insights of Al-Ghazali and Ibnu Miskawaih. The methodology employed is qualitative library research with a comparative-philosophical approach toward the concepts of Tazkiyatun Nafs (Purification of the Soul) and Tahdzib al-Akhlaq (Refinement of Character). The findings indicate that Al-Ghazali emphasizes a